Dampak Kenaikan Harga Bahan Bakar Minyak (BBM) Terhadap Sembilan Bahan Pokok (Sembako) Di Kota Medan - Rozaini, Noni; Harahap, Asshofi Fadhillah (CV. ITTC INDONESIA, 2022)
Fuel Oil (BBM) is a commodity that plays a vital role in all economic activities. The direct impact of this change in oil prices is a change in operational costs which results in a corrected level of profit for direct investment activities. The increase in fuel prices has not only increased the burden on the common people in general but also on the business world in particular. This is due to an increase in production cost items thereby increasing overall costs and resulting in an increase in the cost of production. This study aims to determine the impact of the increase in fuel prices for nine basic commodities. The research method used is descriptive analysis with percentage calculations to determine the composition of the respondents. The data used in this study is by distributing questionnaires to the people in Medan City. The results of the study show that the impact of rising fuel prices (BBM) on staple foods seen from several indicators and respondents' responses includes: a negative impact with a percentage of 90%, it can be concluded that the increase in fuel prices has a negative impact on staple foods in Medan City.